Guidance and Counseling Teachers' Strategies in Handling Bullying Behavior at SMP Negeri 1 Balongan Indramayu - Syifa Nur Fadilah; Siti Aisyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Bullying is the use of power to harm an individual or group, either verbally, physically, or psychologically, leaving the victim feeling depressed, traumatized, and helpless. Adolescents who experience bullying are at greater risk than perpetrators, including mental health problems such as depression, anxiety, and sleep disturbances, which can persist into adulthood. The purpose of this study was to describe and provide a preventative measure to address bullying behavior at SMP Negeri 1 Balongan. This study used descriptive qualitative research, collecting field data from a sample of 88 students from classes 8A, 8C, and 8E, along with relevant sources. The guidance and counseling teacher's strategy for addressing bullying at SMP Negeri 1 Balongan involves providing group guidance services to students to address bullying within the school environment, enabling them to implement these services in their daily lives.